2012
DOI: 10.1007/s00228-012-1227-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and gender on pharmacokinetics and pharmacodynamics of a single ticagrelor dose in healthy individuals

Abstract: Purpose The aim of this study was to assess age and gender effects on ticagrelor pharmacokinetics and pharmacodynamics (PK/PD). Methods Forty healthy individuals [18-45 years (young); ≥65 years (elderly); ten men, ten women per age group) received 200 mg ticagrelor. Results Ticagrelor was rapidly absorbed [time to maximum concentration (C max ) (t max ) 2.5-3.0 h], and its major active metabolite, AR-C124910XX rapidly formed (t max 3.0-3.5 h) in all groups. Ticagrelor exposure was higher in elderly vs. the you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Gender, age, concomitant food intake, preloading with clopidogrel or genetic effects have been reported not to affect ticagrelor absorption or its antiplatelet effect [11, 1921]. On the other hand, AMI patients receiving morphine are at greater risk of attenuated ticagrelor bioavailability and inadequate platelet inhibition [10].…”
Section: Discussionmentioning
confidence: 99%
“…Gender, age, concomitant food intake, preloading with clopidogrel or genetic effects have been reported not to affect ticagrelor absorption or its antiplatelet effect [11, 1921]. On the other hand, AMI patients receiving morphine are at greater risk of attenuated ticagrelor bioavailability and inadequate platelet inhibition [10].…”
Section: Discussionmentioning
confidence: 99%
“…The greatest individual increase in ticagrelor exposure in our homogenous group of healthy young subjects was a more than three‐fold increase in the AUC of ticagrelor. Age, gender, drug interactions and concomitant diseases can affect platelet function, as well as the pharmacokinetics and pharmacodynamics of ticagrelor ; these individual factors may thus modify the magnitude of the grapefruit juice–ticagrelor interaction and its clinical consequences in individual patients. A further caveat is that by increasing ticagrelor exposure, grapefruit juice can prolong the recovery of platelets after ticagrelor dosing, which can be of significance when preparing for surgery , or during management of bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…A dedicated gender study in human subjects is needed to explore any differences in pharmacokinetics, as well as in pharmacodynamics, and in the pharmacokinetic-pharmacodynamic relationship. In a recent study investigating the platelet response to single doses of ticagrelor in elderly and in young females, compared to young males, the authors reported higher platelet sensitivity to treatment in young males than in female and elderly subjects [28]. The effect of various formulations and of the doubleprodrug on the pharmacokinetics of ACT-281959 and ACT-246475 had been investigated in rats and dogs and showed species differences.…”
Section: Discussionmentioning
confidence: 97%